2018
DOI: 10.1007/s12223-018-0619-y
|View full text |Cite
|
Sign up to set email alerts
|

Production and cleavage of a fusion protein of porcine trypsinogen and enhanced green fluorescent protein (EGFP) in Pichia pastoris

Abstract: Pharmaceutical grade trypsin is in ever-increasing demand for medical and industrial applications. Improving the efficiency of existing biotechnological manufacturing processes is therefore paramount. When produced biotechnologically, trypsinogen-the inactive precursor of trypsin-is advantageous, since active trypsin would impair cell viability. To study factors affecting cell physiology and the production of trypsinogen in fed-batch cultures, we built a fusion protein of porcine trypsinogen and enhanced green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Although it is well established that high levels of recombinant protein production affect cell growth, it appears that the reverse may also be true, at least when growth is linked to methanol catabolism. This was in fact demonstrated by intentional growth rate limitation using lower cultivation temperature (Jahic, Wallberg, Bollok, Garcia, & Enfors, ), methanol feeding rates (Raschmanová et al, ; Sinha et al, ), or oxygen levels (Khatri & Hoffmann, ), which all led to higher recombinant protein productivities. It is important to emphasise that these reduced growth rates were accompanied by reduced methanol consumption rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is well established that high levels of recombinant protein production affect cell growth, it appears that the reverse may also be true, at least when growth is linked to methanol catabolism. This was in fact demonstrated by intentional growth rate limitation using lower cultivation temperature (Jahic, Wallberg, Bollok, Garcia, & Enfors, ), methanol feeding rates (Raschmanová et al, ; Sinha et al, ), or oxygen levels (Khatri & Hoffmann, ), which all led to higher recombinant protein productivities. It is important to emphasise that these reduced growth rates were accompanied by reduced methanol consumption rates.…”
Section: Resultsmentioning
confidence: 99%
“…Flow cytometry (FC) was selected to follow the induction of expression as a function of cellular fluorescence and to monitor the behaviour of the population in response to methanol (Broger, Odermatt, Huber, & Sonnleitner, ). Indeed, this convenient combination of reporter protein and analytic tool has recently been used (Raschmanová et al, ), including to develop a methanol biosensor (Takeya, Yurimoto, & Sakai, ). A MutS derivative of the Mut+ strain GS115 was constructed, for the comparison of EGFP production during batch cultivation in bioreactors.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we successfully inserted BORIS sf2 into the plasmid pCS-CG, but weak EGFP protein expression resulted in nearly invisible fluorescence in the cells infected by Lenti-pCS-CG C2/A4. A previous study reported cleavage of the fusion protein containing EGFP as a fusion partner and suggested this was probably caused by the presence of substances that degraded the fusion protein (35). Toca-Herrera et al also pointed out that the intensity of EGFP fluorescence emission was related to temperature, pH conditions, and guanidine hydrochloride concentrations (36).…”
Section: Discussionmentioning
confidence: 99%